The Effect of Sunburn on Fruit Quality of cv. Idared Apple - Racskó, József; Szabó, Zoltán; Lakatos, László; Lőrinczy, Gábor; Nyéki, József (Acta Agraria Debreceniensis, 2006)
The aim of this study is to investigate the effect of sunburn injury on fruit quality parameters (colour-coverage, depth of affected tissue, fruit flesh firmness, soluble solids content) of apple. The symptoms of sunburn injury appeared in concentric ring shape, differed from each other and surface colour-coverage. This can be due to the ratio of the injury. The authors observed the following colours on the fruit surface (from the epicentre of the blotch on the transversal diameter of the fruit) dark brown (strongly affected), light brown (moderately affected), pale red transition (poorly affected), red surface colour-coverage (not affected). Sunburn of apple fruits is a surface injury caused by solar radiation, heat and low air relative humidity that in the initial phase results in a light corky layer, golden or bronze discolouration, and injuries to the epidermal tissue, in the surface exposed to radiation. Thus it detracts from its appearance, but in most cases, it would not cause serious damage to the epidermal tissue. The depth of affected tissue is not considerable, its values are between 1.5-2.0 mm generally. It is commonly known that the tissue structure of apple fruit is not homogeneous. Accordingly, the degree of injury shows some differences under the different parts of the fruit surface. On the basis of flesh firmness research, the authors established that the measure of flesh firmness of the affected part of apple fruit increases with the effect of sunburn. The consequence of this is the suffered plant cells will die, the water content of this tissue decreases and the fruit gets harder. This water-loss caused the increase of soluble solids content.